8(x-6)=-88

Simple and best practice solution for 8(x-6)=-88 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-6)=-88 equation:


Simplifying
8(x + -6) = -88

Reorder the terms:
8(-6 + x) = -88
(-6 * 8 + x * 8) = -88
(-48 + 8x) = -88

Solving
-48 + 8x = -88

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + 8x = -88 + 48

Combine like terms: -48 + 48 = 0
0 + 8x = -88 + 48
8x = -88 + 48

Combine like terms: -88 + 48 = -40
8x = -40

Divide each side by '8'.
x = -5

Simplifying
x = -5

See similar equations:

| -3x+36=-18 | | 6b^2+13b-63= | | 3/4*2/7= | | 8*9n=96 | | 19-(2x+3)=2(x+3) | | 2(x+1)=3x-15 | | 10y-2=3y+33 | | 3(5+4b)-2=0 | | 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W | | 27x^2+37x=0 | | 3=2(-2)-y | | 4x-12=3.5 | | 10+x=1x+2 | | 3(x+4)-2=3x+10 | | 2x-4y+-6=0 | | 6y+15=9y | | 2u+10=20 | | 3b*c= | | 2x^3-12x^2+24x-14=0 | | 8x-x^2-15=0 | | 2x+4=8x-1 | | y+3=4(x-1) | | t^2+3tf-28f^2= | | 2x^3+2x-12=0 |

Equations solver categories